THE INFLUENCE OF INFORMAL ECONOMIC EDUCATION ON THE ECONOMIC BEHAVIOR OF INDONESIAN MIGRANT WORKERS MEDIATED BY ECONOMIC AND ENTREPRENEURIAL LITERACY - Amalina, Endah; Haryono, Agung; Rokhmani, Lisa; Rachmawati, Dian (UNIVERSITAS NEGERI SURABAYA, 2024)
Indonesian Migrant Workers (PMI) ideally have a stable and prosperous economic condition characterized by the ability to manage finances wisely through safe and efficient savings and investments. However, this condition differs from most PMIs, who experience economic difficulties after returning to Indonesia. This study aims to confirm the influence of informal economic education, economic literacy, and entrepreneurial literacy on PMI's economic behavior. This research applies Covariance-Based Structural Equation Modeling (CB-SEM) using a quantitative approach with deductive thinking logic. Data were collected through an online survey and analyzed using IBM-SPSS-AMOS 25 to confirm the hypothesis proposed. The results showed that informal economic education, economic literacy, and entrepreneurial literacy positively affected PMI's economic behavior. Economic and entrepreneurial literacy also mediate the relationship between informal economic education and PMI's economic behavior in a partial (partial mediation) manner. The results provide valuable insights for policymakers and job training institutions on involving families to improve economic and entrepreneurial literacy in encouraging PMI's economic behavior.